2012
DOI: 10.4103/0975-7406.100260
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgical osteotomy for harvesting intraoral block bone graft

Abstract: The use of ultrasonic vibrations for the cutting of bone was first introduced two decades ago. Piezoelectric surgery is a minimally invasive technique that lessens the risk of damage to surrounding soft tissues and important structures such as nerves, vessels, and mucosa. It also reduces damage to osteocytes and permits good survival of bony cells during harvesting of bone. Grafting with intraoral bone blocks is a good way to reconstruct severe horizontal and vertical bone resorption in future implants sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
3
Order By: Relevance
“…Piezosurgery requires much less hand pressure than traditional rotary instruments. 46 The shape of the graft can be accurately removed from the donor site, and donor-site morbidity can be kept as low as possible. Majewski investigated the possibility of harvesting individual bone blocks with an individual piezoelectric cut design.…”
Section: Different Applications In Implantologymentioning
confidence: 99%
“…Piezosurgery requires much less hand pressure than traditional rotary instruments. 46 The shape of the graft can be accurately removed from the donor site, and donor-site morbidity can be kept as low as possible. Majewski investigated the possibility of harvesting individual bone blocks with an individual piezoelectric cut design.…”
Section: Different Applications In Implantologymentioning
confidence: 99%
“…Also, it minimizes osteocytes damage, allowing for faster healing of the lesion [31,32]. The use of such surgical approach in the current study resulted in a 8,3% recurrence rate after prolonged followup, without relevant postoperative side effects such as swelling, paresthesia or pain.…”
Section: Discussionmentioning
confidence: 78%
“…Lakshmiganthan et al. reported that piezoelectric surgery is a minimally invasive technique that lessens the risk of damage to surrounding soft tissues and important structures such as nerves, vessels, and mucosa [22]. It also decreases damage to osteocytes and permits good survival of bony cells during bone harvesting.…”
Section: Discussionmentioning
confidence: 99%